Political competition, campaign contributions and the monopolisation of industries - Peter Michaelis (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1995)
The present paper develops a model of endogenous policy making where a 'low regulation' party / and a 'high regulation' party h compete for campaign contributions spent by a dominating low-cost firm within a regulated industry. The model shows that assuming an endogenous market structure reinforces the economic impacts of lobbying activities compared to the case of a fixed number of firms. In particular, political competition can lead to a level of regulation where all firms using the high-cost technology decide to leave the market such the dominating firm becomes a monopolist. This outcome is c.p. the more likely, the larger the cost differential between the lobbying firm and its high-cost competitors is, and the less external financial sources like, e.g., governmental grants are available to the political parties. Moreover, ideological'constraints that prevent the low regulation party from taking up its equilibrium position will also increase the probability of monopolisation.
Keywords: 330; Regulierung; Interessenpolitik; Industrieökonomik; Marktstruktur; Ökonomische Theorie der Demokratie; Parteienfinanzierung; Umweltauflage; Theorie